2007
DOI: 10.1111/j.1475-6811.2007.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathic accuracy of intimate partners in violent versus nonviolent relationships

Abstract: This study compared the empathic accuracy of men and women who had perpetrated physical intimate partner violence with that of partners in nonviolent but distressed and nonviolent and nondistressed relationships. Examined was the empathic accuracy (a) of partners for one another’s thoughts and feelings during a relationship problem discussion in the laboratory, (b) of partners’ empathic accuracy for each other with the empathic accuracy of objective observers who watched the couples’ interactions, and (c) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
3
34
1
Order By: Relevance
“…Thus, it remains unclear whether Péloquin and colleagues' findings that the association between empathy and IPV is expressed for both men and women, however, solely in actor effects and not partner effects, would generalize to other types of IPV and overall levels of IPV, not only including psychological but also physical and sexual IPV. To the extent that overall levels of empathy are related to levels of empathic accuracy, it is likely that actor and partner effect findings may differ when considering overall IPV because the association between empathic accuracy and physical and verbal and IPV has only been found for men (Clements et al, 2007;Schweinle et al, 2002). In addition, the samples used in previous research to explore the association between empathy and IPV were relatively small and thus warrant replication in a larger and nationally representative sample of couples.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, it remains unclear whether Péloquin and colleagues' findings that the association between empathy and IPV is expressed for both men and women, however, solely in actor effects and not partner effects, would generalize to other types of IPV and overall levels of IPV, not only including psychological but also physical and sexual IPV. To the extent that overall levels of empathy are related to levels of empathic accuracy, it is likely that actor and partner effect findings may differ when considering overall IPV because the association between empathic accuracy and physical and verbal and IPV has only been found for men (Clements et al, 2007;Schweinle et al, 2002). In addition, the samples used in previous research to explore the association between empathy and IPV were relatively small and thus warrant replication in a larger and nationally representative sample of couples.…”
mentioning
confidence: 85%
“…Empathic accuracy describes dyad members' ability to read and understand their partners' affective and cognitive state accurately (Clements, Holtzworth-Munroe, Schweinle, & Ickes, 2007). In a study of 71 heterosexual couples in committed relationships, Clements et al (2007) tested the notion that, relative to nonviolent partners, physically violent partners would be poor interpreters of one another's thoughts and feelings. Results showed that violent men were significantly less accurate at inferring their female partner's thoughts and feelings than were nonviolent, nondistressed men.…”
mentioning
confidence: 99%
“…As with the ESS, the MSAS was found to be associated with adaptive social behaviors, including skillful support (Verhofstadt, Buysse, Ickes, Davis, & Devoldre, 2008), reduced intimate partner violence (Clements, Holtzworth-Munroe, Schweinle, & Ickes, 2007), and positive relationship feelings in romantic couples (Rafaeli et al, under review).…”
Section: Interpersonal Perception and Interpersonal Difficultiesmentioning
confidence: 96%
“…Other studies show a negative association between empathy and IPV (e.g. Clements, Holtzworth-Munroe, Schweinle & Ickes, 2007) and same-sex aggression (e.g. Miller & Eisenberg, 1988) although a more recent meta-analysis found only a weak overall negative relationship between empathy and aggression, which varied little by type of aggression or empathy measure (Vachon, Lynam & Johnson, 2014).…”
Section: Self-controlmentioning
confidence: 98%